1979
DOI: 10.1113/jphysiol.1979.sp012947
|View full text |Cite
|
Sign up to set email alerts
|

Development of spinal reflexes in the rat fetus studied in vitro.

Abstract: SUMMARY1. The onset and development of spinal reflex activity was investigated using the isolated spinal cord of the rat fetus. The potential changes generated in motoneurones were recorded extracellularly from L3 ventral roots.2. A spike potential was recorded from the ventral root at embryonic day 13-5 in response to stimulation of the cord surface close to the ventral root. The discharge persisted in Ca2+-free solution but was blocked by tetrodotoxin.3. At embryonic day 14-5, trans-synaptically evoked disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 31 publications
5
64
1
Order By: Relevance
“…In the present study the estimated central delay for the stretch reflex at all ages was similar to, or shorter than, those in adults, with 540 DEVELOPMENT OF PHASIC STRETCH REFLEX the implication that the early component of the phasic stretch reflex is monosynaptic during development. This conclusion receives direct support from developmental studies in animals where the phasic stretch reflex has been shown to have a monosynaptic component in both fetus and newborn (rat: Saito, 1979;Kudo & Yamada 1987;cat: Wilson, 1962;Skoglund, 1960;Eccles & Willis, 1965).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the present study the estimated central delay for the stretch reflex at all ages was similar to, or shorter than, those in adults, with 540 DEVELOPMENT OF PHASIC STRETCH REFLEX the implication that the early component of the phasic stretch reflex is monosynaptic during development. This conclusion receives direct support from developmental studies in animals where the phasic stretch reflex has been shown to have a monosynaptic component in both fetus and newborn (rat: Saito, 1979;Kudo & Yamada 1987;cat: Wilson, 1962;Skoglund, 1960;Eccles & Willis, 1965).…”
Section: Discussionmentioning
confidence: 84%
“…Excitatory reflex actions from muscle afferents predominate (Skoglund, 1960; Saito, 1979; Myklebust, 1990). The kitten has been shown to have excitatory monosynaptic projections between primary afferents and cc-motoneurones of non-homonymous and non-synergistic muscles, which become greatly reduced in comparison to the adult cat (Eccles, Shealy & Willis, 1963).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, although a direct comparison between two species cannot be made, neuromuscular junctions containing a synaptic vesic1e antigen have been observed at ED 14 in another rodent species, the mouse. '9 In the rat, the motor neurons become excitable around ED 14 28 and electrical as weil as chemical excitability appear one week before birth. 20 The first evidence for functional synaptic transmission within rat intercostal musc1es was reported to occur at ED 15: 6 i.e.…”
Section: Synaptophysin Transcription and Translation Precedes Synapsementioning
confidence: 99%
“…Cutaneous afferents appear in rat proximal hindlimb on embryonic days 14 -15 (E14 -E15) and in skin of distal toes at E16 -E17 (Reynolds et al, 1991;Mirnics and Koerber, 1995). These fibers are functional slightly later, beginning at E17 (Saito, 1979;Kudo and Yamada, 1985;Fitzgerald, 1987;Kucera et al, 1988;Fitzgerald, 1991). Neuropeptides appear around the time of peripheral target functional contacts (E18 -E19) (Kessler and Black, 1981;Senba et al, 1982), suggesting that target interactions could influence sensory neuronal phenotype.…”
mentioning
confidence: 99%